Haematopoietic Stem Cell Transplantation in Children Shifts the Coagulation System towards a Pro-Coagulant State - Långström, Satu; Koskenvuo, Minna; Huttunen, Pasi; Lassila, Riitta; Taskinen, Mervi; Ranta, Susanna; Heikinheimo, Markku; Mäkipernaa, Anne (Thrombosis and Haemostasis, 2018)
Coagulation system is disturbed by several mechanisms after allogeneic haematopoietic stem cell transplantation (HSCT). We evaluated the effect of HSCT on coagulation system by various conventional and investigational methods in 30 children and adolescents who received HSCT due to haematological malignancies. Pro-thrombin fragment 1 + 2, a specific measure of thrombin generation, and von Willebrand factor, a measure of endothelial activation, increased after conditioning treatment, and remained elevated until 3 months after HSCT (p < 0.05 for all comparisons to pre-conditioning treatment). D-dimer, a measure of fibrin turnover, was elevated from the second week onwards until 4 weeks after HSCT (p < 0.05). Endogenous thrombin potential was increased after conditioning, and at 2 weeks after HSCT (p < 0.05). Furthermore, the activities of acute phase reactants fibrinogen and coagulation factor VIII were increased (p < 0.05 for all comparisons to pre-conditioning treatment) from the first week onwards up to 3 weeks and 3 months after HSCT, respectively. Taken together, paediatric patients receiving HSCT demonstrate distinct and prolonged variations in the coagulation system towards a pro-coagulant state. This shift is of importance when estimating the risk of haemostatic and thrombotic complications in these children.
Keywords: coagulation; paediatric; stem cell transplantation; haematological malignancy; thrombin